Dealing with COVID-19 in Ghanaian urban shared low-income housing: What it reveals and the planning implications - Addo, I.A.; Atobrah, D.; Frehiwot, M.; Kwansa, B.K. (Cities, 2023)
Compound and shared low-income houses in Ghana have economic, social, cultural, and familial advantages. Yet, COVID-19 and its related lockdown and home confinement in two urban cities, Accra and Kumasi, raised questions about the appropriateness of staying in a compound house while observing the COVID-19 protocols. Whereas a few studies have underscored the ineffectiveness of COVID-19 protocols in low-income shared houses, these assume a homogeneity of such households without reflecting on the diversities that exist among and be tween the different categories of low-income households and the imperative nuanced implications for the spread of infectious diseases. Against this backdrop the paper employed qualitative methodologies of in-depth in terviews and non-participant observations to interrogate the experiences of low-income households’ utilisation of space as they observed COVID-19 protocols. Drawing respondents from four low-income communities in Accra, the authors examined how traditional family households and non-traditional family households implemented the safety protocols and their implications for shared housing. Issues of sharing inadequate communal facilities and public health concerns as well as lack of access to inadequate water and living spaces impacted the respondents’ COVID-19 experience. The study discovered that households’ socioeconomic status is directly related to the management of epidemics in urban spaces in Ghana.
Research Article
Keywords: COVID-19; Compound house; Shared low-income housing